2015
DOI: 10.1007/s00268-015-2961-4
|View full text |Cite
|
Sign up to set email alerts
|

The SF‐36 and 6‐Minute Walk Test are Significant Predictors of Complications After Major Surgery

Abstract: SF-36 (Physical Functioning) and 6-MWT are useful indicators for predicting postoperative complications and LOS. Patients undergoing major surgery answered SF-36 and performed 6-MWT. Physical Functioning as a component of the SF-36 correlated with LOS. The 6-MWT had a negative correlation with LOS and with complication grade. SF-36 and 6-MWT are useful predictors of postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
1
32
2
3
Order By: Relevance
“…The survey addresses two main components: mental health and physical functioning. The reliability of the SF‐36 has been rigorously tested and verified in Sheffield, England . Heydecke et al found that functional limitations, physical pain, physical limitations and mental disability dimensions in SF‐36 were important variables for OHRQoL and oral health effects in elderly patients receiving implant therapy and prosthetic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The survey addresses two main components: mental health and physical functioning. The reliability of the SF‐36 has been rigorously tested and verified in Sheffield, England . Heydecke et al found that functional limitations, physical pain, physical limitations and mental disability dimensions in SF‐36 were important variables for OHRQoL and oral health effects in elderly patients receiving implant therapy and prosthetic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Evidence regarding the ability of the 6MWT to predict patient outcomes in the perioperative setting is limited to cohort studies with sample sizes of approximately 100 patients. In patients having thoracic or major general surgery, the 6MWT distance was predictive of postoperative complications 7,9,10 and hospital length of stay 10,11 in some but not all studies, 12 and was predictive of mortality in patients undergoing bilateral lung volume reduction surgery for severe chronic airways disease. 11 Its ability to predict cardiovascular or patientcentred outcomes in a large surgical cohort is not known.…”
mentioning
confidence: 96%
“…In der Praxis kann diese Leistungsfähigkeit auch mit einfacheren Tests, wie z. B. Steep-ramp-Test und Gehtests (6Minuten-Gehtest [6MWT]), ohne den Gasaustausch gemessen werden [21,22]. Außerdem können auch andere Tests, wie der Stair-rise-time-und Handgrip-strength-Test, zur Vorhersage der postoperativen Mortalität und beim Entlassungsmanagement verwendet werden [23,24].…”
Section: High-risk Patients · Physical Fitness · Risk Stratification unclassified